Formulação de modelos constitutivos de degradação isotrópica para representação do comportamento bimodular do concreto - Guilherme Ribeiro Caetano (2022)
Concrete is a structural material used on a large scale in civil construction. Its durability, malleability and strength make it a material preferred by engineers. Then, studying its characteristics and behavior is of great importance for structural projects. The constitutive modeling of concrete has been investigated by several authors, however, it is not a very simple task. Concrete is a heterogeneous material and, in addition, in tension regimes, concrete presents a different mechanical behavior compared to the compression regimes. It is also known that its compressive strength is superior to its tensile strength. This asymmetric behavior of concrete in tension and compression is called bimodularity. To model this complex behavior, one of the ways is through the continuum damage theory that relates the progressive loss of stiffness of the material through an internal variable called damage. This variable indicates the level of degradation of the material media. Usually, the damage models that represent the bimodular behavior of concrete adopt two damage variables to represent the degradation by tension and compression. In this work, isotropic degradation models are formulated, with independent parameters and laws of tension and compreension, in such a way that they provide better parameterization of bimodular materials.